Pengembangan Model Pembelajaran Berdiferensiasi Membaca Teks Eksposisi Berbasis Activity-Based Learning: Development of an Activity-Based Learning Model for Differentiated Reading Instruction of Expository Texts - Maimunah Maimunah; Miftahulkhairah Anwar; Gusti Yarmi (ITScience (Information Technology and Science), 2026)
Instruction in reading expository texts at the junior high school level (SMP/MTs) continues to face various challenges, particularly students' low reading comprehension in interpretative and critical aspects. Furthermore, conventional teaching methods—often applied uniformly to all students—fail to accommodate differences in learning readiness, interests, and learning styles. This situation necessitates the development of an instructional model capable of addressing the diverse learning needs of students in heterogeneous classrooms. This study aimed to develop a differentiated reading instruction model for exposition texts for Grade VIII students at MTs Attaqwa Pusat Putri. The study employed the Research and Development (R&D) method using the ADDIE model, comprising the stages of analysis, design, development, implementation, and evaluation. The developed products included a teaching module, student learning materials, a teacher's handbook, and